Renal angiomyolipoma with renal vein thrombosis: an incidental finding - Abreu, Elisa Melo; Cunha, Teresa Margarida (BJR I case reports, 2016)
A 66-year-old female with history of endometrioid endometrial carcinoma was admitted to our institution with abdominal and pelvic pain. A CT scan revealed a mass within the right upper kidney with a tumour thrombus that extended through the right renal vein up to the point of confluence with the inferior vena cava (IVC). The imaging features of the mass strongly suggested a diagnosis of renal angiomyolipoma (AML) with renal vein thrombosis. The patient was proposed an open radical right nephrectomy with right renal thrombectomy for histopathological confirmation of the diagnosis of AML with extension to the right renal vein and preventing complications such as potentially fatal pulmonary thromboembolism. The implantation of a temporary IVC filter before surgery was recommended.